Behind the Knowledge and Attitude: Female Adolescent in Looking at Physical Appearance Change during Puberty at SMPN 1 Telaga Biru Gorontalo - Zuriati Muhamad; Fatmah Zakaria; Anik Indarwaty; Happy Anastasia (PSPP JOURNALS, 2021)
As a period of life, the adolescence is an important stage that a person must go through before he reaches adulthood. During adolescence, many changes occur both biologically, psychologically and socially. Generally, the process of physical change occurs faster than mental maturation. The changes in physical appearance that occur in adolescents can cause anxiety and awkwardness for adolescents because they require them to adjust to the changes that occur. This study aimed to analyze the relationship between knowledge and attitudes of young women in preparing for physical appearance changes during puberty in SMP Negeri 1 Telaga Biru, Gorontalo District, Gorontalo Province, Indonesia. This type of research is a quantitative study with a cross sectional approach. The population in this study were all of the 163 female junior high school students of SMP Negeri 1 Telaga Biru 1 in Gorontalo. The sampling technique used stratified random sampling on grade VII to IX students. The obtained samples were 54 students. Data processing was analyzed using chi square test. Based on the research results, it was found that the relationship between the knowledge of young women in dealing with physical changes at puberty was p value = 0.009 < 0.05. Second, there is a relationship between the attitudes of young women in dealing with physical changes at puberty with the results of the chi square test showing the p value = 0.007 < 0.05. The conclusion of this study is that there is a relationship between adolescent knowledge in dealing with physical changes at puberty and there is a relationship between adolescent attitudes in dealing with physical changes at puberty. Researchers expect that in dealing with changes during puberty, adolescents must equip themselves with knowledge and have a positive attitude.